Silica-Polymer Composites as the Novel Antibiotic Delivery Systems for Bone Tissue Infection - Adrianna Skwira; Adrian Szewczyk; Agnieszka Konopacka; Monika Górska; Dorota Majda; Rafał Sądej; Magdalena Prokopowicz (MDPI AG, 2019)
Bone tissue inflammation, osteomyelitis, is commonly caused by bacterial invasion and requires prolonged antibiotic therapy for weeks or months. Thus, the aim of this study was to develop novel silica-polymer local bone antibiotic delivery systems characterized by a sustained release of ciprofloxacin (CIP) which remain active against Staphylococcus aureus for a few weeks, and do not have a toxic effect towards human osteoblasts. Four formulations composed of ethylcellulose (EC), polydimethylsiloxane (PDMS), freeze-dried CIP, and CIP-adsorbed mesoporous silica materials (MCM-41-CIP) were prepared via solvent-evaporation blending method. All obtained composites were characterized in terms of molecular structure, morphological, and structural properties by using Fourier Transform Infrared Spectroscopy (FTIR), scanning electron microscopy equipped with energy-dispersive X-ray spectroscopy (SEM/EDX), and X-ray diffraction (XRD), thermal stability by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC), and in vitro antibiotic release. The antibacterial activity against Staphylococcus aureus (ATCC 6538) as well as the in vitro cytocompatibility to human osteoblasts of obtained composites were also examined. Physicochemical results confirmed the presence of particular components (FTIR), formation of continuous polymer phase onto the surface of freeze-dried CIP or MCM-41-CIP (SEM/EDX), and semi-crystalline (composites containing freeze-dried CIP) or amorphous (composites containing MCM-41-CIP) structure (XRD). TGA and DSC analysis indicated the high thermal stability of CIP adsorbed onto the MCM-41, and higher after MCM-41-CIP coating with polymer blend. The release study revealed the significant reduction in initial burst of CIP for the composites which contained MCM-41-CIP instead of freeze-dried CIP. These composites were also characterized by the 30-day activity against S. aureus and the highest cytocompatibility to human osteoblasts in vitro.